ITG Workshop on Smart Antennas (IEEE Cat. No.04EX802)
DOI: 10.1109/wsa.2004.1407674
|View full text |Cite
|
Sign up to set email alerts
|

Overloaded TDD-CDMA cells with multiuser transmission

Abstract: The number of supportable users in the TDD- [I]. All MUT methods have the constraint that the transmit CDMA downlink is usually limited by multipleaccess interference and by lbe limited number of available orthogonal spreading codes. By using Multiuser Transmission (MUT) methods in the base station in conjunction with smart antennas, the interference can be mitigated and the downlink cell capacity can be substantiallv increased. The number of snonorted users signal power is limited. Linear Zero-Forcing MUT (Tx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Provided that the desired main tap (53) and (54) Note that the main tap c d must be known in any receiver, i.e. the dth column of the system matrix H must be known in the receiver.…”
Section: Extension To Qammentioning
confidence: 99%
See 1 more Smart Citation
“…Provided that the desired main tap (53) and (54) Note that the main tap c d must be known in any receiver, i.e. the dth column of the system matrix H must be known in the receiver.…”
Section: Extension To Qammentioning
confidence: 99%
“…The MBER filtering design has also been incorporated into turbo iterative detection [51][52][53]. Other applications include the MBER transmission schemes [54][55][56], the MBER rake receiver [57,58], the MBER-based optical receiver [59][60][61][62], and the power control or allocation based on the MBER criterion [63][64][65][66]. It can be seen that the introduction of the novel MBER design has opened up a new research direction and has stimulated wide interests in the communication research community.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the FCLI algorithm is investigated by computer simulations using the OFDM system parameters of the WIGWAM home/office (HO) or public access (PA) scenarios [6] listed in Table 1. or a practical distribution of timing errors.…”
Section: Fcli Channel Estimation Performancementioning
confidence: 99%
“…Similarly, the noise-free part of the th detector's output assumes values from the set (24) Thus can only take the values from the set (25) and can be divided into the two subsets conditioned on the value of (26) The conditional probability density function (pdf) of given is a Gaussian mixture given by [15], [16] …”
Section: Minimum Bit Error Rate Multiuser Detectionmentioning
confidence: 99%
“…For the single-user single-antenna system, the minimum BER (MBER) equalization design has become popular [17]- [24], and it has been shown that the MBER DFE is less sensitive to the error propagation due to decision feedback errors compared to the MMSE DFE [24]. For the base station employing multiple transmit antennas, an MBER multiuser transmission scheme has been proposed in [25], while for the multiple antenna assisted receiver, an MBER rake receiver has been discussed in [26]. Against this background, the novelty of this paper is that the MBER ST DFE assisted MUD (ST-DFE-MUD) is proposed for the first time in the literature in the context of SDMA.…”
mentioning
confidence: 99%